Overcoming the Barrier of Low Efficiency during Genetic Transformation of Streptococcus mitis - Salvadori, Gabriela; Junges, Roger; Morrison, Donald A.; Petersen, Fernanda C. (Frontiers in Microbiology, 2016)
Objective: Streptococcus mitis is a predominant oral colonizer, but difficulties in genetic manipulation of this species have hampered our understanding of the mechanisms it uses for colonization of oral surfaces. The aim of this study was to reveal optimal conditions for natural genetic transformation in S. mitis and illustrate its application in direct genome editing. Methods: Luciferase reporter assays were used to assess gene expression of the alternative sigma factor (σX) in combination with natural transformation experiments to evaluate the efficiency by which S. mitis activates the competence system and incorporates exogenous DNA. Optimal amounts and sources of donor DNA (chromosomal, amplicon, or replicative plasmid), concentrations of synthetic competence-stimulating peptide, and transformation media were assessed. Results: A semi-defined medium showed much improved results for response to the competence stimulating peptide (CSP) when compared to rich media. The use of a donor amplicon with large homology flanking regions also provided higher transformation rates. Overall, an increase of transformation efficiencies from 0.001% or less to over 30% was achieved with the developed protocol. We further describe the construction of a markerless mutant based on this high efficiency strategy. Conclusions: We optimized competence development in S. mitis, by use of semi-defined medium and appropriate concentrations of synthetic competence factor. Combined with the use of a large amplicon of donor DNA, this method allowed easy and direct editing of the S. mitis genome, broadening the spectrum of possible downstream applications of natural transformation in this species.